Стильные штучки из бисера - Ляукина Марина Викторовна (Ручная работа, 2006)
Экземпляры: ф.22 (2011) / Инвентарный номер: 53733 / Цена: / Сис.шифр: 85.125 / Авт.знак: Л 97 / ГРНТИ: 18.31.51 / ББК: 37.248